2013
DOI: 10.1007/s40333-013-0190-y
|View full text |Cite
|
Sign up to set email alerts
|

Response of ants to grazing disturbance at the central Monte Desert of Argentina: community descriptors and functional group scheme

Abstract: Livestock ranching is one of the main productive activities in arid regions of the world. Grazing produces changes in animal as well as plant communities (e.g. richness, abundance and species dominance relationships). Ants are good biological indicators due to the environmental fidelity of some of their community parameters. We described the functional structure of the ant community in the central Monte of Mendoza, Argentina, and examined the effect of grazing using richness, diversity and the functional group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 18 publications
3
9
0
1
Order By: Relevance
“…; Claver et al . ). These groups were: Dominant Dolichoderinae (species of Dorymyrmex and Forelius ), Subordinate Camponotini (species of Camponotus ), Tropical‐Climate Specialists (TCS) (mostly Attini and Wasmannia auropunctata ), Hot‐Climate Specialists (species of Pogonomyrmex ), Cryptic Species (mostly species of Solenopsis subgenus Diplorhoptrum and Hypoponera ), Opportunists (species of Brachymyrmex , Ectatomma, Nylanderia and Gnamptogenys ), Generalized Myrmicinae (species of Pheidole and Crematogaster ) and Specialist Predators (species of Odontomachus , Pachycondyla and Neoponera ).…”
Section: Methodsmentioning
confidence: 97%
“…; Claver et al . ). These groups were: Dominant Dolichoderinae (species of Dorymyrmex and Forelius ), Subordinate Camponotini (species of Camponotus ), Tropical‐Climate Specialists (TCS) (mostly Attini and Wasmannia auropunctata ), Hot‐Climate Specialists (species of Pogonomyrmex ), Cryptic Species (mostly species of Solenopsis subgenus Diplorhoptrum and Hypoponera ), Opportunists (species of Brachymyrmex , Ectatomma, Nylanderia and Gnamptogenys ), Generalized Myrmicinae (species of Pheidole and Crematogaster ) and Specialist Predators (species of Odontomachus , Pachycondyla and Neoponera ).…”
Section: Methodsmentioning
confidence: 97%
“…Ant species richness is usually correlated with primary productivity estimated on the basis of annual precipitation (Davidson 1977), and IPP comprises a hyper-arid area with scarce vegetation cover and low precipitation (Márquez et al 2005). In the Man and Biosphere Reserve of Ñacuñan (province of Mendoza), a protected area of the central plains and plateaus Monte Desert ecoregion, located 400 km southeaster from IPP and with three times more precipitation, Claver et al (2014) found 27 ant species in an open forest of Prosopis flexuosa. Similarly, in the Sierra de Las Quijadas National Park (province of San Luis), a protected area located 300 km southern from IPP in the ecotone between the plains and plateaus Monte Desert and Dry Chaco ecoregions, with a higher precipitation and vegetation cover than IPP, Garcia and Quirán (2002) found only 23 species.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we calculated the diversity of response traits within each functional group (Table 2) using Rao's coefficient (Botta-Dukát, 2005). In order to accurately measure response diversity in our system, we chose response traits related to grazing tolerance, with low intraspecific variation (Díaz et al, 2007;Chillo and Ojeda, 2012;Claver et al, 2014). Almost all trait values were recorded from published sources and information, except for small mammal's weight and the trend in abundance trait, which were calculated from sampling data.…”
Section: Discussionmentioning
confidence: 99%
“…Ants were sampled using four pitfall traps (9 cm diameter) placed in a 2 Â 2 grid, 40 m apart each and active during three consecutive days. During a previous sampling session, this effort demonstrated to be enough to capture similar species richness as previous studies (Claver et al, 2014). Small mammals were sampled using Sherman live-capture traps, placed in a 4 Â 4 grid, 10 m apart each and active during three consecutive nights.…”
Section: Data Collectionmentioning
confidence: 92%